Antimicrobial Peptides from Fruits and Their Potential Use as Biotechnological Tools—A Review and Outlook - Meneguetti, Beatriz T.; Machado, Leandro dos Santos; Oshiro, Karen G. N.; Nogueira, Micaella L.; Carvalho, Cristiano M. E.; Franco, Octávio L. (Frontiers in Microbiology, 2017)
Bacterial resistance is a major threat to plant crops, animals and human health, and over the years this situation has increasingly spread worldwide. Due to their many bioactive compounds, plants are promising sources of antimicrobial compounds that can potentially be used in the treatment of infections caused by microorganisms. As well as stem, flowers and leaves, fruits have an efficient defense mechanism against pests and pathogens, besides presenting nutritional and functional properties due to their multifunctional molecules. Among such compounds, the antimicrobial peptides (AMPs) feature different antimicrobials that are capable of disrupting the microbial membrane and of acting in binding to intra-cytoplasmic targets of microorganisms. They are therefore capable of controlling or halting the growth of microorganisms. In summary, this review describes the major classes of antimicrobial peptides found in fruits, their possible use as biotechnological tools and prospects for the pharmaceutical industry and agribusiness.